How effectively bonding evolution theory retrieves and visualizes curly arrows: The cycloaddition reaction of cyclic nitrones. Issue 19 (29th May 2019) - Adjieufack, Abel I.; Mbah Bake, Maraf; Ketcha Mbadcam, Joseph; Mbouombouo Ndassa, Ibrahim; Andrés, Juan; Oliva, Mónica; Safont, Vicent S.
Abstract: In the present work, the electron density flows involved throughout the progress of the four reaction pathways associated with the intramolecular [3 + 2] cycloaddition of cyclic nitrones Z‐1 and E‐1 are analyzed using the bonding evolution theory. The present study highlights the nonconcerted nature of the processes, which can be described as taking place in several stages. The first stage consists in the depopulation of the initial CN and CC double bonds to render the N lone pair and the corresponding CN and CC single bonds, and these electronic flows initiate the reactions. The CC and CO sigma bond formations take place later on, once the transition states have been overcome. Along the bridged pathways, the CC bond formation process precedes the OC bond formation event, although, along the fused paths, the OC bond formation process occurs first and the formation of the CC bond is the last electronic flow to take place. Finally, curly arrow representations accounting for the timing of the electron flows are obtained from the bonding evolution theory results. Abstract : A chemical reaction involves the transformation of the electronic structure of the reactants into that of the products, via the corresponding transition state. The bonding evolution theory is capable of describing this transformation by recovering the curly arrows representation and the timing of the electron density flows along the reaction progress. Here, the intramolecular [3 + 2] cycloadditions of cyclic nitrones are selected as case study.